Impact of Agri‐Usable Nanocompounds on Soil Microbial Activity: An Indicator of Soil Health. Issue 5 (16th March 2017) - Khati, Priyanka; Sharma, Anita; Gangola, Saurabh; Kumar, Rajeew; Bhatt, Pankaj; Kumar, Govind
Abstract : Soil quality of agriculture fields has been significantly influenced by rapid industrialization and pollution which has affected crop productivity and quality. Carbon based formulations of some nanocompounds are finding their way in the agriculture sector due to positive response on plant health. The present study revealed the impact of three agri‐usable nanocompounds (being used in an agricultural field of the University since the last 4–5 years on different cropping systems) on soil health on the basis of physicochemical characters, microbial activities, indicator enzymes, and total extractable protein. Nanocompounds used in the fields were nanoclay, nanochitosan, and nanozeolite with a size of <80 nm, 99% purity with an application rate of 0.03 g/1.5 L ha −1 . Nanoclay had little effect on the pH of soil. The level of available phosphorus, organic carbon and ammoniacal nitrogen was higher in all the soil samples treated with nanocompounds than the control. All the nanocompounds supported microbial population. Significant increase in the activities of dehydrogenase, fluorescein diacetate, alkaline phosphatase, amylase, arylesterase, and β‐glucosidase was observed in soil samples treated with nanocompounds. Total protein concentration of treated soil was also enhanced by 1.5‐fold as compared to control. The performance of nanozeolite was found best with all the parameters. The finding of the present study suggest that the nanocompounds support microbial activity and hence the soil health. Abstract : To evaluate soil health, the direct indicators such as nutrients, enzymes, proteins, and microorganisms of soil are analyzed. The results imply that nanocompound application enhances soil health.